2019
DOI: 10.12957/reuerj.2019.40537
|View full text |Cite
|
Sign up to set email alerts
|

Os determinantes da qualidade de vida em pessoas com HIV: uma revisão integrativa

Abstract: Objetivo: analisar os determinantes que afetam a qualidade de vida de pessoas com HIV, a partir da revisão de pesquisas originais. Método: revisão integrativa da literatura com busca de produção sobre os determinantes da qualidade de vida de pacientes com HIV nas bases de dados PubMed, Scopus, CINAHL, CUIDEN e PsycINFO, realizada em abril de 2018. Resultados: foram identificadas 22 pesquisas, publicadas no período de 2012 a 2016. Detectou-se dispersão dos determinantes (42 variáveis) da qualidade de vida dessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(128 reference statements)
0
2
0
1
Order By: Relevance
“…Conversely, we can associate this issue with advances and greater accessibility to HIV treatment, which has reduced early mortality from the disease, and the affected people are able to have a better quality of life 27 . Authors of an integrative literature review evaluated the determinants of the quality of life of people living with HIV and the most cited variables in the studies are social support, depression, stigma, and adherence to treatment 28 . Another study, whose authors evaluated the quality of life of older people with HIV, observed that the years of living with the disease have a positive influence on quality of life, considering that time is necessary for there to be an adaptation to the changes caused by this condition 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, we can associate this issue with advances and greater accessibility to HIV treatment, which has reduced early mortality from the disease, and the affected people are able to have a better quality of life 27 . Authors of an integrative literature review evaluated the determinants of the quality of life of people living with HIV and the most cited variables in the studies are social support, depression, stigma, and adherence to treatment 28 . Another study, whose authors evaluated the quality of life of older people with HIV, observed that the years of living with the disease have a positive influence on quality of life, considering that time is necessary for there to be an adaptation to the changes caused by this condition 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Social support describes the extent to which social connections help mitigate the negative consequences of disease [ 19 ]. Social support is essential to stress management in health-related crises [ 20 ] and, specifically, to the dimensions of HIV management [ 21 , 22 , 23 ] such as prevention, adherence to treatment and recovery [ 20 ]. Several studies have highlighted the association between social support and QoL in disease (e.g., [ 24 ]).…”
Section: Introductionmentioning
confidence: 99%
“…cial, a depressão, o estigma e a aderência ao tratamento28 .Outro estudo, que avaliou a qualidade de vida de pessoas idosas com HIV, observou que os anos de convivência com a doença tem influência positiva na qualidade de vida, uma vez que o tempo é necessário para que haja adaptação às mudanças por esse agravo29 .Os resultados encontrados neste estudo destacam a delimitação das áreas com maior concentração dos casos nas regiões metropolitanas e litoral sul, justamente as mais populosas do estado. Além disso, também há concentração de casos nas regiões de São José do Rio Preto, Ribeirão Preto, Sul de Araraquara e Vale do Paraíba Paulista, que abrigam grande parcela da população no interior do estado.…”
unclassified